Analytical modeling and analysis of workload allocation in a network of service centers - Rahela Rahim,; Ku Ruhana Ku Mahamud, (Penerbit UKM, 2006)
Redesign of business processes is currently attracting a lot of interest. Although many tools and technique have been used to model such processes, less attention is given to the analytical aspect to support or optimize the redesign process. In other application areas, where a network of server systems are concerned such as computer and communication systems, telecommunication systems and manufacturing systems, many analytical techniques have been developed to analyze the temporal aspect of the systems. The similarities exist between these kinds of system and business processes. An analytic approach is presented that considers the performance of business process designs. A close-loop expression is derived from a non-linear optimization problem to obtain an optimal value for jobs arrival.